Traceable Value for Proficiency Test of Natural Gas - Ridwan, Yohanes Susanto; Supriadi, Supriadi; Nugraha, Willy Cahya (Indonesian Journal of Science and Technology, 2019)
The use of consensus values as the assign value for proficiency testing (PT) activities are currently a common practice in Indonesia, including the field of natural gas analysis. Hence, mostly the performance evaluation is based on consensus agreement. In this work, a PT was conducted using traceable values with respectÂ  to ISO/IEC 17043 and ISO 13528. It was demonstrated that the chosen PT scheme has good capability to evaluate the performance of participating laboratories. And, in some cases, the selected PT scheme was not affected by extreme values and limited number of participants. Post analysis to the PT round has been conducted using the information of uncertainty of the traceable value and the uncertainty of robust average of participantsâ€™ results. It was demonstrated that there were no significance biases in the PT round. Moreover, it could be concluded that the participating laboratories have a good agreement with one to another. They also have a good agreement with traceable values, giving more additional confidence to the measurement quality in this field of analysis.